Sizing and location of shunt FACTS devices in power system using genetic algorithms (2011)
FACTS (Flexible AC Transmission Systems) devices are used to improve different problems in a power system. In this work, a Genetic Algorithm (GA) is used to solve a multi-objective optimization problem which consists of finding the optimal size and location of the shunt FACTS devices. The objective is to enhance both voltage stability margin and first swing stability margin in a multi-machine power system. The analysis is done for important contingencies that cause problems both for voltage stability margin and first swing stability margin. In this new method the location and sizing of shunt FACTS devices are optimized simultaneously. Two different kinds of shunt FACTS devices are used for transient and steady-state studies: Static Var Compensator (SVC) and Static Synchronous Compensator (STATCOM). The proposed method is evaluated on a 68 bus test system. The results obtained show that proposed algorithm can find the optimal location and sizing of shunt FACTS devices in a power system.